Desain LNG Storage Tank dan Sistim Refrigerasinya untuk Mobil Berbahan Bakar Gas - Rudianto Rudianto; Anis Mustaghfirin Muh.; Mahardhika Pekik (Proceedings Conference on Marine Engineering and its Application, 2018)
LNG or liquified natural gas is gas that used as fuel in industrial sector. LNG gas has critical point -1180C. But when it’s used on cramped vehicle, it’s needed special cryogenic tank to keep LNG temperature. Therefore,it needs to be designed LNG storage tank in gas- fuelled car with PV elite software. Previous research has already been conducted on the LNG- fuelled truck. This study purpose to created a tank design support equipment and cascade refrigeration system with LMTD method. This tank was made to save and survive the existance of LNG fuel. The design calculation result of refrigeration system has obtained 4 stage cascade system.Refrigerant used is 134a, Ethane, methane, and Ethylane. Cooling load is very small 28,77 Watts, so can be used small compressor 1/10 PK.The heat exchanger design are obtained at stage bottom-up use ¼ in copper pipe wuth a leght 8,5 cm, 8,51 cm, 11,53 cm, and 18,58 cm. And capillary pipe design is obtained frome bottom-up stage with diameter 0, 26 in, 0,31 in, 0,33 in, 0,31 in, and 0,59 in with lenght 3,8 m, 1,2 m, 1,4 m, 1,9 m, and 4,6 m.